2008
DOI: 10.1016/j.ccm.2007.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Functional Imaging: CT and MRI

Abstract: Synopsis-Numerous imaging techniques permit evaluation of regional pulmonary function. Contrast-enhanced CT methods now allow assessment of vasculature and lung perfusion. Techniques using spirometric controlled MDCT allow for quantification of presence and distribution of parenchymal and airway pathology, Xenon gas can be employed to assess regional ventilation of the lungs and rapid bolus injections of iodinated contrast agent can provide quantitative measure of regional parenchymal perfusion. Advances in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 193 publications
0
52
0
Order By: Relevance
“…HRCT imaging detects early emphysema by identifying pulmonary tissue with radiologic attenuation below a predetermined threshold, findings that roughly correlate with a low DL CO and pathologic evidence of emphysema (74)(75)(76)(77)(78)(79)(80). Although several studies have shown that a significant proportion of asymptomatic smokers have HRCT evidence of emphysema (78,(81)(82)(83), early HRCT findings of ''emphysema'' are not proven to be correlated directly with lung destruction (84)(85)(86)(87)(88)(89)(90).…”
Section: Early Detection Of Lung Destructionmentioning
confidence: 99%
“…HRCT imaging detects early emphysema by identifying pulmonary tissue with radiologic attenuation below a predetermined threshold, findings that roughly correlate with a low DL CO and pathologic evidence of emphysema (74)(75)(76)(77)(78)(79)(80). Although several studies have shown that a significant proportion of asymptomatic smokers have HRCT evidence of emphysema (78,(81)(82)(83), early HRCT findings of ''emphysema'' are not proven to be correlated directly with lung destruction (84)(85)(86)(87)(88)(89)(90).…”
Section: Early Detection Of Lung Destructionmentioning
confidence: 99%
“…Imaging techniques used in the diagnosis of sarcoidosis include CT (in the case of pulmonary sarcoidosis, HRCT: high resolution computerised tomography), MRI [magnetic resonance imaging (with gadolinium contrast)] and FDG-PET (positron emission tomography with Xuoro-2-deoxy-D-glucose) [61][62][63]. Imaging examinations via 67-radiogallium citrate scintigraphy is also used for the diagnosis of sarcoidosis [1][2][3][4][5][6][7][8]44].…”
Section: Diagnosismentioning
confidence: 99%
“…To estimate lung perfusion, various approaches for determining blood flow and mean transit time have been described using dynamic CT (52,53). The main focus thus far has been related to the visualization of perfusion defects in pulmonary embolism or the characterization of lung tumors.…”
Section: Functional Imagingmentioning
confidence: 99%